Vaspin Alleviates Sepsis-Induced Cardiac Injury and Cardiac Inflammation by Inhibiting Kallikrein 7 in Mice - Na Yin; Fuze Pan; Lingyue Qiu; Zicong Yang; Rixin Xiong; Lei Shi; Ying Shi; Ning Wu; Kui Wu; Qingkuan Li; Daojun Wen; Qili Huang; et al. (Hindawi Limited, 2022)
Background. Vaspin is an important adipokine that is involved in cardiovascular diseases. This study is aimed at investigating whether vaspin participates in sepsis-induced cardiac injury and explored the possible mechanism. Methods. First, cecal ligation and puncture (CLP) and lipopolysaccharide (LPS) were used to establish a mouse model of sepsis, and cardiac vaspin expression was examined. In addition, after pretreatment with vaspin or phosphate-buffered saline (PBS), wild-type (WT) mice underwent CLP to establish a septic model and received sham as a control. Finally, WT mice and kallikrein 7 (KLK7-/-) mice were underwent CLP with or without vaspin pretreatment. Results. Mice that underwent CLP and were administered LPS exhibited increased vaspin expression in both the heart and serum compared with sham- or saline-treated mice. In CLP mice, pretreatment with vaspin reduced mortality and alleviated the expression of cardiac injury markers and cardiac dysfunction. In addition, vaspin reduced the cardiac levels of CD45+ cells and CD68+ cells, alleviated the cardiac inflammatory response, and reduced cardiomyocyte apoptosis. The protective effects of vaspin on CLP mice were masked by the deletion of KLK7, which was demonstrated to be a downstream signal of vaspin. Conclusions. Vaspin alleviates cardiac inflammation and plays a protective role in sepsis-induced cardiac injury by reducing KLK7 expression.